Classifying player positions in second-tier Australian football competitions using technical skill indicators - Barake, A. J.; Mitchell, H.; Stavros, C.; Stewart, M. F.; Srivastava, P. (International Journal of Sports Science & Coaching, 2022)
Efficient recruitment to Australias most popular professional sporting competition, the Australian Football League (AFL), requires evaluators to assess athlete performances in many lower tier leagues that serve as pathways. These competitions and their games are frequent, widespread, and challenging to track. Therefore, independent, and reliable player performance statistics from these leagues are paramount. This data, however, is only meaningful to recruiters from AFL teams if accurate player positions are known, which was not the case for the competitions from which most players were recruited. This paper explains how this problem was recently solved, demonstrating a process of knowledge translation from academia to industry, that bridged an important gap between sports science, coaching and recruiting. Positional information which is only available from the AFL competition was used to benchmark and develop scientific classification methods using only predictor variables that are also measured in lower tier competitions. Specifically, a Multinomial Logistic model was constructed to allocate players into four primary positions, followed by a Binary Logit model for further refinement. This novel technique of using more complete data from top tier competitions to help fill informational deficiencies in lower leagues could be extended to other sports that face similar issues.